2012
DOI: 10.1155/2012/727843
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Local Administration of Aminophylline on Transureteral Lithotripsy

Abstract: Introduction. Urinary stone is a common cause of urinary tract disease. Stone excretion using ureteroscope is effective in inferior ureter. The aim of this study was to investigate the effects of aminophylline on ureteral spasm during ureteroscopy in acute phase of renal colic. Methods. In this double-blind randomized clinical trial, 120 patients with ureteral stones were enrolled and randomized into two groups. The bladder was drained and then received a 150 mL irrigation solution. Irrigation solution was sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 7 publications
1
10
1
Order By: Relevance
“…In their study using a local injection of aminophylline during trans-urethral lithotripsy, Baregarnezhad et al showed that aminophylline facilitates the uretroscopy procedure, increases the success rate for the treatment of renal colic by using (transurethral lithotripsy), decreases operative time, and reduces the need for a double J catheter and wave lithotripsy (45). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study using a local injection of aminophylline during trans-urethral lithotripsy, Baregarnezhad et al showed that aminophylline facilitates the uretroscopy procedure, increases the success rate for the treatment of renal colic by using (transurethral lithotripsy), decreases operative time, and reduces the need for a double J catheter and wave lithotripsy (45). …”
Section: Resultsmentioning
confidence: 99%
“…Its mechanism is through the inhibition of a non-selective phosphodiesterase inhibitor that; increases the concentration of intracellular cAMP, activates PKA (protein kinase A), inhibits TNF-α and the synthesis of leukotrienes, and reduces inflammation. Non-selective antagonism of adenosine receptors is the second mechanism ( 45 ). Aminophylline is a well-known drug and it is widely used in the treatment of renal colic ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Barzegarnezhad et al, reported that local administration of aminophylline during TUL leads to 95% success rate in interventional [9] group as compared to placebo (72%) . Mulay et al, reported that aminophylline group did not [11] show any side effects similar to our study .…”
Section: Resultsmentioning
confidence: 99%
“…Barzegarnezhad et al reported that aminophylline is associated with high success rate in renal colic patients with transureteral lithotripsy. Aminophylline leads to several benefits including decrease process duration, decrease stone migration towards kidney, [9] reduce ureteral and catheter (double J) need . Djaladat et al reported that aminophylline is an effective drug is pain relief and reduce narcotic usage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation